2020
DOI: 10.1016/j.bja.2020.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia and COVID-19: infection control

Abstract: The world is currently facing an unprecedented healthcare crisis caused by a pandemic novel beta coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pathogen is spread by human-to-human transmission via droplets exposure and contact transfer, causing mild symptoms in the majority of cases, but critical illness, bilateral viral pneumonia, and acute respiratory distress syndrome (ARDS) in a minority. Currently, controlling infection to prevent the spread of SARS-CoV-2 is the primary pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0
20

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 55 publications
1
100
0
20
Order By: Relevance
“…The protection level of the surgical gowns depends on the type of procedure [76] . An filtering face pieces (FFP) 2 mask filters 94% of all particles that are 0.3 mm in diameter or larger; while N95 masks block 95% and FFP3 masks block 99% [77] . A class 2 or 3 FFP face mask should be worn when working in close contact with patients with suspected or confirmed COVID-19, and only to use surgical face masks in a crisis scenario of shortage of FFP 2 and 3 respirators [78] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protection level of the surgical gowns depends on the type of procedure [76] . An filtering face pieces (FFP) 2 mask filters 94% of all particles that are 0.3 mm in diameter or larger; while N95 masks block 95% and FFP3 masks block 99% [77] . A class 2 or 3 FFP face mask should be worn when working in close contact with patients with suspected or confirmed COVID-19, and only to use surgical face masks in a crisis scenario of shortage of FFP 2 and 3 respirators [78] .…”
Section: Discussionmentioning
confidence: 99%
“…Airborne transmission risks are high during aerosol generating procedures such as laparoscopy, endoscopy and tracheal incubation to exposure patients' oropharynx and airway secretions with a high viral load [79] . We suggest that surgical team members, including anesthesiologists, surgeons and operating nursing staff should ware highly protective levels of PPE when treating patients known to have been infected with COVID-19 [77] . Most recent information from Italy reported that 12% of healthcare workers were infected at the beginning of COVID-19 pandemic [67] , and this incidence was greatly reduced when PPE was used properly and infection control measures were followed [80] .…”
Section: Discussionmentioning
confidence: 99%
“…An additional consideration is that CPET does not incorporate bacterial and viral filters to collect exhaled particles. The potential to produce infected droplets from a positive COVID-19 patient will increase the risk of both airborne and surface transmission 14,15 and needs consideration regarding the potential for protracted viral shedding (i.e. the test lasts <10 min).…”
Section: Precautions and Risk Mitigation For Cpet Testingmentioning
confidence: 99%
“…Early intubation before transport should be considered for patients requiring-high flow oxygen (>15 L/min) or noninvasive ventilation. 3 Patients may be transported on low-flow oxygen sources (such as nasal cannula, simple facemask, or non-rebreather mask). Face masks should be worn by the patient, including over any airway devices.…”
mentioning
confidence: 99%
“…Early intubation before transport should be considered for patients requiring-high flow oxygen (>15 L/min) or noninvasive ventilation. 3 …”
mentioning
confidence: 99%